Bolesław Wicherkiewicz and his role in the development of new cataract surgery techniques in the late XIX century - Bogdali, Anna; Jarczak, Jakub; Ciszewski, Bartłomiej; Mackiewicz, Natalia; Szworak, Martyna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Professor Bolesław Wicherkiewicz (1847–1915) was a prominent Polish ophthalmologist considered one of the best in Europe. Initially, he stayed in Poznań where he set up the largest ophthalmic hospital in the 19th-century Poland. In 1896, he was appointed Professor of Ophthalmology and the Head of Ophthalmology Department at the Jagiellonian University in Cracow. Bolesław Wicherkiewicz’s research focused mainly on surgical methods and techniques in cataract, glaucoma, epicanthic fold, and small palpebral fissures, as well as the introduction of new drugs in ophthalmology, and treatment of ocular inflammatory diseases. In 1885, he initiated the use of a 10% solution of cocaine for local anaesthesia instead of general anaesthesia with chloroform. He developed a method for the anterior capsule removal using four-tooth forceps, also used in cataract surgery with simultaneous iridectomy. Bolesław Wicherkiewicz initiated immature cataract removal using a self-invented irrigation device to rinse the eye with 1–2% boric acid solution. At his own expense, he also published the first Polish ophthalmic magazine, Postęp Okulistyczny , in 1899–1914. Published works of Boleslaw Wicherkiewicz amount to about 300 publications in Polish, German, English, and French. Professor Wicherkiewicz was a great patriot and his love for the homeland was manifested repeatedly in his activities in both divided Poland and internationally.